Variation of resistance to chloride penetration of iron-rich phosphoaluminate cement with admixture materials subjected to NaCl environment. (20th January 2020) - Wang, Shoude; Zhang, Wenlong; Zhang, Shuxin; Lu, Lingchao; Cheng, Xin
Highlights: The addition of AMs could improve significantly the resistance to chloride penetration of hardened paste of iron-rich PAC. Corresponding, their appropriate addition content of limestone powder, gypsum and silica fume was 6%, 2% and 4%, respectively. The formation of C4 ACH11 and C2 ASH8 could optimize the ITZ area between AMs and hardened paste of PAC. Abstract: Iron-rich phosphoaluminate cement (iron-rich PAC) is one new type of special cement with good mechanical property and durability, which is promising to prepare inorganic coating materials and protect marine engineering. In this paper, the variation of resistance to chloride penetration of the mortars for iron-rich PAC with admixture materials (AMs), including limestone powder, gypsum and silica fume, was investigated carefully. Experimental results showed that the addition of AMs could improve significantly the resistance to chloride penetration of the mortars of iron-rich PAC. This was contributed to the decrease of porosity and reduction of pore size of the mortars of iron-rich PAC with the addition of AMs. Their appropriate addition content was 6% of limestone powder, 2% of gypsum and 4% of silica fume, respectively. Also, some new hydration products of calcium carbonaluminate hydrate (C4 ACH11 ) and stratlingite (C2 ASH8 ) were formed, which could optimize the ITZ area between AMs and hardened paste in the iron-rich PAC mortars.